Driving Health Innovation: The Dynamics of Strategic Learning and Quality Management in Product Development - Gall, Dylan (My University, 2026)
The intent of this study is to underscore the critical features of what drives innovation capabilities within business in the startup phase. Within the contents of this thesis, findings are derived from the case study of OTO, a startup company based out of Toronto, Canada and seeking to rapidly develop innovative technologies within the health technology industry. After the acquisition of Omegawave, a health technology company based out of Espoo, Finland, OTO began a change management process based around underlying strategic direction towards a new market and the effort to improve product quality, of which this paper will investigate in detail. Two core areas of research will be discussed. Firstly, the role of strategic learning in innovation contexts. Secondly, product-level quality management in innovative contexts. A qualitative single case methodology was employed within this study, allowing in depth investigation into the strategic perspective and company aims. Different perspectives on these topics are explored through semi structured interviews, enabling a nuanced examination of how OTO’s strategic learning and quality management choices shape its innovation capabilities. Findings result from the perspective of OTO related to the interplay of the two main areas of research, and its results on creating an innovative product within OTO. The intent of translating OTO’s innovation capabilities to an innovative product, as well as maintaining a high standard of quality for the consumer are critical components of technology firms and remain an area that is greatly influenced by many variables, both internal and external to the company in question. This paper’s intent is to conduct a study that contributes to theoretical understanding of what important attributes derived from the areas of strategic learning and quality management have the largest impact on innovation capabilities.
Keywords: enterprises; innovations; organisations (systems); quality management; leadership (activity); strategies; strategic leadership; learning; self-evaluation; product development; business models; fi=Johtaminen ja organisaatiot|en=Management and Organization|; Master’s Programme in Strategic Business Development